WELL VERTICAL DRAINAGE AS METHOD FOR DECREASING OF EXOGGEODYNAMIC ACTIVITY ON SLOPE AREAS - Kuzmenko, E.; Yakovlev, E.; Davybida, L.; Zinchenko, V.; Nikitash, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The territory of Mezhyhirya on the right bank of the Kiev reservoir, which is characterized by the development of various dangerous exogenous geological processes, primarily landslides and flooding, is being considered as the object of research. The purpose of the research is to substantiate the method of artificially lowering of groundwater level within the flooded areas of Mezhyhirya with a corresponding decrease in risk of landslide activity. In the course of the research, an analysis of general and specific factors of the activation of landslides within the Mezhyhirya area was carried out, and its results proved that most of these factors are related to natural and technogenically disturbed hydrogeological conditions of the research area. The authors have determined the sources of technogenic feeding, the zones of increased moisture within the natural boundary, as well as the directions and structure of groundwater transit to the territory of Mezhyhiria. The performed studies and their results confirm the need to reduce the saturation of aquifers and, accordingly, the exo-geodynamic activity of rocks within the territory of Mezhyhirya. The technical solution was based on the drilling of vertical drainage wells connecting the quaternary ground and the Obukhov-Mezhygorsk collector aquifer. Hydrogeological calculations of the water volume of the daily drainage of the involved wells were performed, which must have been about 104 m3/day. Three observation wells were involved for monitoring the decrease in the piezometric level of groundwater. Control observations of groundwater levels confirmed an effectiveness of the proposed scheme; however, during the spring upsurge of 2013, vertical drainage wells did not ensure complete interception of the filtration flow. A possible reason for this is the increase in the hydrodynamic load of the groundwater aquifer due to irrigation and leakage from lakes. At subsequent stages of research, mapping of filtration flows seems appropriate. The data obtained as a result of the study can serve as the basis for designing a set of solutions for drainage of the aquifer and anti-landslide measures within the territory of Mezhyhirya.